PROGRAM PENGEMBANGAN WISATA ALAM DANAU GUMANG GANAM DI BAWAH SALURAN UDARA TEGANGAN TINGGI DI DESA OBEL-OBEL - Yadnya, Made Sutha; Misbahhuddin, Misbahhuddin; Zainuddin, Abdullah; Paniran, Paniran; Ramadhani, Cipta; Nasir, Abdul; Muljono, Agung Budi (Universitas Mataram, 2024)
The development of tourist destinations in Lombok is growing very quickly. The tourist attraction of Gumbang Ganang Lake Tourism Village in Obel-Obel Village is a tourist attraction with extraordinary uniqueness because right above it is the High Voltage Air Line owned by PT. PLN. Currently, data has begun to be recorded with the Pokdarwis group. There are challenges that need to be fixed, namely the problem of explaining the radiation from SUTT. If it is done correctly, nothing detrimental will happen, and waste handling is still carried out sporadically without any storage tanks. This is overcome by providing outreach and handling directly to this tourist destination. In this program, which has been implemented in a very short time, it has provided progress in knowing and being directly involved in Obel-Obel Village so that the development of tourism in the vein of SUTT right above the lake provides CSR and contribution from PT. PLN.